Gene Expression Profiling of Corpus luteum Reveals Important Insights about Early Pregnancy in Domestic Sheep - Pokharel, Kisun; Peippo, Jaana; Weldenegodguad, Melak; Honkatukia, Mervi; Li, Meng-Hua; Kantanen, Juha (MDPI AG, 2020)
The majority of pregnancy loss in ruminants occurs during the preimplantation stage, which is thus the most critical period determining reproductive success. Here, we performed a comparative transcriptome study by sequencing total mRNA from corpus luteum (CL) collected during the preimplantation stage of pregnancy in Finnsheep, Texel and F1 crosses. A total of 21,287 genes were expressed in our data. Highly expressed autosomal genes in the CL were associated with biological processes such as progesterone formation (STAR, CYP11A1, and HSD3B1) and embryo implantation (e.g., TIMP1, TIMP2 and TCTP). Among the list of differentially expressed genes, sialic acid-binding immunoglobulin (Ig)-like lectins (SIGLEC3, SIGLEC14, SIGLEC8), ribosomal proteins (RPL17, RPL34, RPS3A, MRPS33) and chemokines (CCL5, CCL24, CXCL13, CXCL9) were upregulated in Finnsheep, while four multidrug resistance-associated proteins (MRPs) were upregulated in Texel ewes. A total of 17 known genes and two uncharacterized noncoding RNAs (ncRNAs) were differentially expressed in breed-wise comparisons owing to the flushing diet effect. The significantly upregulated TXNL1 gene indicated potential for embryonic diapause in Finnsheep and F1. Moreover, we report, for the first time in any species, several genes that are active in the CL during early pregnancy (including TXNL1, SIGLEC14, SIGLEC8, MRP4, and CA5A).
Keywords: suomenlammas; texel; keltarauhanen; progesteroni; transkriptio (biologia); lammas; hedelmällisyys; Finnsheep; progesterone; preimplantation; embryonic diapause